Reinforcement Of Soft Soil Using Soil Column Method (Soft Soil + CCR + RHA) - Dwi Wahyuni; Dewi Ratna; Saloma Saloma (Sriwijaya Journal of Environment, 2021)
Soil reinforcement method is one of attempt to improve technical characteristic from the soil, such as soil bearing capacity, compressibility and permeability. The Soil Column Method is one of alternatives to enhance physical characteristic by way of stabilization to improve soil bearing capacity. Rice Husk Ash (RHA) contains high silica element, Calcium Carbide Residue (CCR) contains high calcium which is able to form pozzolan when mixed upon silica. This research aims to improve soil bearing capacity by using column soil method with a mixture of soft soil, 3% Calcium Calbide Residue (CCR) and 12% Rice Husk Ash (RHA). Soil column in this research applied a single column variation with a diameter of 3,2 cm which each has 40 cm, 46 cm, and 53 cm in length and each column with diameter of 3,2 cm, 4,2 cm, and 4,8 cm. Based on the research, ultimate Bearing Capacity (qu) of soft soil without soil column was 54,03 kPa and after being given reinforcement had increased the bearing capacity value (qu). The greates increase in soil bearing capacity of the soft soil occurred in soil column variation of 53 cm in lenght with 4,8 cm in diameter where the soil bearing capacity had increased to 75,58 kPa and the percentage increase in BCR was 39,90%. Meanwhile the least of soil bearing capacity occurred in soil column that had 53 cm in length and diameter of 3,2 cm while the soil bearing capacity had increased to 64,47 kPa and BCR only increased to 19,33%